2003
DOI: 10.1002/gps.1022
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of neuropsychological change in individuals with Parkinson's disease

Abstract: Consistent with previous studies, executive function tasks were those most susceptible to disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 31 publications
4
34
1
1
Order By: Relevance
“…Some studies have indicated that a verbal fluency decline is associated with PD [36]. Although this deficit might appear to be a potential confound in our study, we found that when performing the COWAT, the subjects with RHO did not differ from those with LHO but when examining verbal creativity these groups did differ.…”
Section: Discussioncontrasting
confidence: 78%
“…Some studies have indicated that a verbal fluency decline is associated with PD [36]. Although this deficit might appear to be a potential confound in our study, we found that when performing the COWAT, the subjects with RHO did not differ from those with LHO but when examining verbal creativity these groups did differ.…”
Section: Discussioncontrasting
confidence: 78%
“…Severe damage to the autonomic, limbic, and somatomotor systems that began in the presymptomatic phase can become compounded by supervening functional deficits on the part of the cerebral cortex (Azuma et al 2003).…”
Section: Stages 5 Andmentioning
confidence: 99%
“…Executive function has been reported to be most susceptible to progression [30]. However, it is unknown, which brain regions relate to the functional decline.…”
Section: Longitudinal Changes In Sequence Learningmentioning
confidence: 99%